When Art History gets into a Psychiatrist Hospital - Felipe Cares Villegas; Francisca Ramírez Ibarra (Arteterapia)
This article is an analysis of the first session of an Art History workshop, developed in a school placed in a Psychiatrist Hospital in Santiago de Chile. The students were patients with severe mental disorders. Here we explain our previous work, some questions and problems that we had with the development of the workshop and our experience with the artistic education and the social integration.